New insights in treatment of primary aldosteronism: A narrative review: New insights in treatment of primary aldosteronism - Fakhrul Alam, Mohammad; Jahan, Sharmin; Hasanat, Muhammad Abul; Fariduddin, Md (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
For the last two decades, we are observing an evolution in our understanding of primary aldosteronism (PA). It is now established that PA has remarkably more adverse cardiovascular and renal impact as compared to essential hypertension because of blood pressure independent deleterious effect of aldosterone. But still it is frequently under-recognized and under-treated. When diagnosed, PA can be adequately managed with widely available mineralocorticoid receptor antagonists (MRAs) and/or unilateral adrenalectomy. Steroidal MRAs are highly effective but often under prescribed and can be poorly tolerated because of adverse effects. New generation non-steroidal MRAs like finerenone and esaxerenone have shown promising results on adverse cardiovascular and renal sequelae among patients with diabetic kidney disease and heart failure. They also have favourable safety profile than steroidal MRAs. Though their efficacy regarding blood pressure control and renin normalization remain unclear, non-steroidal MRAs specially finerenone might fulfill the unmet needs of optimum management of PA. In this article we discuss an up-to-date overview on existing treatment of PA and new therapeutic approach, paying attention to its practical implementation into our day-to-day practice. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2024; 3 (1): 22-30